2014
DOI: 10.1155/2014/182362
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic and Antioxidant Potential of Paeonia emodi Royle against High-Fat Diet Induced Oxidative Stress

Abstract: The present study was intended to evaluate the effects of Paeonia emodi rhizome extracts on serum triglycerides (TGs), total cholesterol (TC), low density lipoprotein cholesterol (LDL-c), high density lipoprotein cholesterol (HDL-c), atherogenic index (AI), superoxide dismutase (SOD), and glutathione peroxidase (GPx). The plant was extensively examined for its in vitro antioxidant activity, and the preliminary phytochemical screening was carried out using standard protocols. Male Wistar rats were induced with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…ER stress-signaling pathways regulated by GRP78, leading to UPR survival, cell fate and apoptosis responses [45]. ER stress induces XBP-1 to produce a more active transcription factor [46].…”
Section: Discussionmentioning
confidence: 99%
“…ER stress-signaling pathways regulated by GRP78, leading to UPR survival, cell fate and apoptosis responses [45]. ER stress induces XBP-1 to produce a more active transcription factor [46].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it must be highlighted that the presence of antioxidants and their effective in vitro scavenging capacities are also positively correlated with the protective effects of plant extracts against various disturbances, such as prevention of cell damage caused by UV light exposure [51], antineoplastic effects on tumor cell lines [52,53], reduction of the oxidative stress in animals models of hyperlipidemia [54,55] and liver injuries [56,57], among others.…”
Section: Resultsmentioning
confidence: 99%
“…19 Apart from this in-vitro study, invivo studies conducted by Zaidi et al, in pentylenetetrazol (PTZ) induced epilepsy and Zargar et al, in high fat dietinduced oxidative stress model have demonstrated antioxidant activity of PEW. 9,20 The doses of the PEW, 200mg/kg/b.w. (low dose, LD) and 300mg/kg/b.w.…”
Section: Discussionmentioning
confidence: 99%
“…This antioxidant effect of ethanolic extract of PEW is also supported by previous studies in vitro as well in vivo studies. 9,19 It is reported that on intra-striatal administration of 6hydroxydopamine, the dopaminergic neurons are specifically degenerated by increased oxidative stress and apoptosis. PEW in higher dose showed protective effect on striatal neurons with clear texture of striatal tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation